Prevalencia de la posición de terceras molares mandibulares según la clasificación de Winter y la clasificación de Pell y Gregory en pacientes de 18 a 35 años de la clínica odontológica docente de la Universidad Peruana de Ciencias Aplicadas durante el periodo febrero 2011-diciembre 2012 - Palacios Colán, Margot Betsabe (2014)
Objective: To determine the prevalence of the lower third molar position according to the classification of Winter and the classification of Pell and Gregory in patients between 18-35 years of age of the Universidad Peruana de Ciencias Aplicadas Dental Clinic during the period from February 2011 to December 2012. Material and methods: This is an observational, descriptive, transversal and retrospective study in which 582 panoramic x-rays were selected of the clinical record of patients that were found in the range of age required and in the establish period of time. Results: 1067 lower third molars were evaluated. According to the study it was observed that the most prevalent positions, according to the classification of Winter were vertical (42, 3 %) and mesioangular (31, 4 %), for both male and female and in both sides for patients between 18 and 35 years. According to the classification of Pell and Gregory, the most prevalent position was IA (39 %) for both genders and in both sides for patients between 18 and 35 years too. Conclusions: According to the classification of Winter the most prevalent positions were the vertical and mesioangular. According to the classification of Pell and Gregory, it was IA. It was also found that those positions were the most frequent in both genders and in both sides for patients between 18 and 35 years.